Innovation of Interactive Multimedia Based on Guided Inquiry Using Articulate Storyline 3 as A Learning Media for Carbon and Silicone Materials in Non-Metal Inorganic Chemistry Courses - Sri Nur Afrida; Retno Dwi Suyanti; Ajat Sudrajat (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to develop interactive multimedia based on guided inquiry on carbon and silicon materials for non-metal inorganic chemistry courses using Articulate Storyline 3 software based on BSNP. This research is a development research (R&D) with the ADDIE model. The sample in this study were lecturers at the State University of Medan, Faculty of Mathematics and Natural Sciences majoring in Chemistry as many as 3 people as validators of media and material experts that were tailored to the needs. The research instrument was in the form of a BSNP questionnaire filled out by material expert validators and media expert validators. Data were analyzed descriptively qualitatively. The results showed that guided inquiry-based interactive multimedia on carbon and silicon materials with an average score of 3.67 and included in the "very feasible" criteria for use on carbon and silicon materials in non-metal inorganic chemistry learning